Semeabilidade, coinoculação e relação causa e efeito na cultura da soja - Burg, Giovane Matias (2021)
Seeding is defined as the precision of seed distribution in the seeding row. Adaptations related to sowing speed and the use of biological nitrogen fixation are technologies capable of influencing soybean grain yield. The aim of this study was to evaluate the relationship between sowing speed and coinoculation on soybean yield and nodulation components. The experiment was carried out according to a randomized block design and the treatments were distributed in a bifactorial (2 x 5), coinoculation (with and without) and five sowing speeds, with four replications. The experiments were carried out in three cultivation places (Santa Maria, Restinga Sêca and Novo Machado), and in two places the evaluations were carried out for two years, and in a city for one year. There was an interaction between sowing speed and co-inoculation on soybean grain yield. The highest yields were obtained at speeds from 2,2 to 5,3 km h-¹. Coinoculation increases the number of nodules (83.47%), the mass of nodules per plant (65.45%) and soybean grain yield (from 140 to 220 kg ha-¹) as a function of sowing speed. For greater uniformity and distribution of plants in the row, the ideal speed is between 1.0 to 3.2 km h-¹. Seeding speed < 5,2 km h-¹ and coinoculation promote increases in soybean grain yield.